(untitled) (Research, Society and Development, 2021)
The sharing of care between the Primary Health Care (PHC) and Specialized Care teams favors the progressive qualification of professionals working in primary care, increasing their resolving capacity and scope of action, in addition to providing a reduction in referrals for the Specialized Care. This study aimed to describe the development of a smartphone application, called IntegRAS, designed to provide a communication channel between general practitioners working in PHC and endocrinologists. Secondarily, it is proposed to carry out a pilot usability test of IntegRAS with volunteer doctors from APS and a university hospital. After surveying the functional requirements and defining the project architecture, the application was developed using multi-platform technology (Android and iOS) and made available in a trial version to five medical professionals, 2 specialists and 3 generalists, for a period of 90 days. Usability questionnaires were sent to the participants with reference to the System Usability Scale (SUS). The developed application acted as a tool to support clinical decision making for general practitioners in PHC. The SUS questionnaire presented scores from 87.5 to 95, giving IntegRAS an excellent rating on the usability scale and supporting it, with its interface and current characteristics, as an efficient technological resource in the integration between health teams. The IntegRAS was an instrument to aid in the assistance to medical practice, with the potential to be useful in continuing health education for general practitioners of PHC.